2019
DOI: 10.1038/s12276-019-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin promotes apoptotic cell death via upregulation of Nrf2 expression by DNA demethylase and the interaction of Nrf2 with p53 in human colon cancer cells

Abstract: Luteolin, a dietary flavone, modulates various signaling pathways involved in carcinogenesis. In this study, we investigated the molecular mechanism that underlies the apoptotic effects of luteolin mediated by DNA demethylation of the nuclear factor erythroid 2-related factor 2 (Nrf2) promoter and the interaction of Nrf2 and p53, a tumor suppressor, in human colon cancer cells. Luteolin increased the expression of apoptosis-related proteins and antioxidant enzymes. In DNA methylation, luteolin inhibited the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 41 publications
2
69
1
Order By: Relevance
“…However, other studies have demonstrated that luteolin can induce the demethylation of the Nrf2 gene promoter region, upregulate the Nrf2 gene expression, activate the Nrf2/ARE pathway, increase the antioxidant capacity, inhibit the transformation and promote apoptosis of colon cancer cells (52,53), which is not supported by the results of the present study. In the current study, it was speculated that the antioxidant capacity served a different role at different stages of cancer development.…”
Section: Discussioncontrasting
confidence: 99%
“…However, other studies have demonstrated that luteolin can induce the demethylation of the Nrf2 gene promoter region, upregulate the Nrf2 gene expression, activate the Nrf2/ARE pathway, increase the antioxidant capacity, inhibit the transformation and promote apoptosis of colon cancer cells (52,53), which is not supported by the results of the present study. In the current study, it was speculated that the antioxidant capacity served a different role at different stages of cancer development.…”
Section: Discussioncontrasting
confidence: 99%
“…Luteolin is a member of the naturally occurring flavonoid family and has various beneficial bioactivities. Numerous studies have revealed anti-inflammatory, antioxidative, anti-apoptotic, autophagic-regulatory, anti-viral, anticancer, and metabolic effects of luteolin, which have been confirmed in many different disease models (Hu et al, 2016;Zhang et al, 2016;Peng et al, 2017;Du et al, 2018;Liu et al, 2018;Tan et al, 2018b;Yang et al, 2018b;Kang et al, 2019). In addition, in studies on ischemic stroke (Qiao et al, 2012;Tan et al, 2018a;Luo et al, 2019), traumatic brain injury (Xu et al, 2014), neurodegenerative diseases (Kwon, 2017;Zhang et al, 2017), and other neurological diseases, luteolin has been shown to exert therapeutic effects.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we demonstrated that luteolin enhanced the activation of the Nrf2 pathway and enhanced Nrf2 nuclear translocation after ICH. Nrf2 is known to regulate various antioxidant enzymes to protect cells against oxidative stress and is essential for the clearance of hematomas (Zhao et al, 2015;Kang et al, 2019). Numerous studies have demonstrated that activation of the Nrf2 signaling pathway is beneficial in alleviating ICH-induced SBI.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, it was observed an increased expression of DNA demethylases, TET (ten eleven translocation) enzymes, combined with TET1 physical interaction with Nrf2 promoter. The interaction between Nrf2 and p53 proteins seems to be important for the induction of apoptosis [128].…”
Section: Luteolinmentioning
confidence: 99%